Marine technology and sustainable development : green innovations - 584040 Olanrewaju, Oladokun Sulaiman author; Saharuddin, Abdul Hamid editor; Ab Saman Ab Kader editor; Mohd Norsani Wan Nik, Wan editor (Hershey, PA : Information Science Reference, an imprint of IGI Global, 2014)
"This book examines theoretical frameworks and empirical research in the maritime industry, evaluating new technologies, methodologies, and practices against a backdrop of sustainability"--